Moderating Effect of Parents Alive on the Relationship between Psychological Resilience and Mental Health - Hassan Bhat, Rizwan; Mohd. Khan, Shah (International Journal of Psychosocial Rehabilitation, 2020)
It has been observed throughout the study that there is a significant correlation between psychological resilience and mental health in the presence of the variable ‘parents alive’, which was taken as a moderator. The moderation analysis technique has been used to determine the referent effect of parents alive on the relationship between psychological resilience and mental health. Three hundred youth were taken to complete the study. The main aim of the study was to examine the moderating effect of parents alive on the relationship between psychological resilience and mental health.Parents alive were found to have a significant moderating effect on the relationship between psychological resilience and mental health. The interaction plot showed the aggravating effect of psychological resilience on mental health. The effectiveness of the moderator variable in determining the correlation will be discussed.